Corollarium Technologies - Gnecco, Bruno Barberi (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
Corollarium is a company that specializes in web and mobile development, image processing, virtual and augmented reality. Its expertise encompasses the full development process - from design to production to installation, aiming to offer customized solutions of the highest quality and lowest maintenance. This paper goes briefly over what we have been researching and creating over the last years.